Aeroelastic coupling analysis of the flexible blade of a wind turbine. (September 2015) - Mo, Wenwei; Li, Deyuan; Wang, Xianneng; Zhong, Cantang
Abstract: This paper presents an aeroelastic coupling analysis of the flexible blade of a large scale HAWT (horizontal axis wind turbine). To model the flexibility of the blade more accurately, 'SE' (super-element) is introduced to the blade dynamics model. The flexible blade is discretized into a MBS (multi-body system) using a limited number of SEs. The blade bending vibration and torsional deflection are both considered when calculating the aerodynamic loads; thus, the BEM (blade element momentum) theory used in this study is modified. In addition, the B–L (Beddoes–Leishman) dynamic stall model is integrated into the BEM-modified model to investigate the airfoil dynamic stall characteristics. The nonlinear governing equations of the constrained blade MBS are derived based on the theory of MBS dynamics coupling with the blade aerodynamics model. The time domain aeroelastic responses of the United States NREL (National Renewable Energy Laboratory) offshore 5-MW wind turbine blade are obtained. The simulation results indicate that blade vibration and deformation have significant effects on the aerodynamic loads, and the dynamic stall can cause more violent fluctuation for the blade aerodynamic loads compared with the steady aerodynamic model, which can considerably affect the blade fatigue load spectrum analysis and the fatigue life design. Highlights: We realize blade aeroelastic coupling simulation using fewer degrees of freedom. We apply super-element to model blade bending and torsional deflections. The Beddoes–Leishman dynamic stall model is integrated into the BEM-modified model. Blade vibration and torsional deformation can affect blade aerodynamic loads. Airfoil dynamic stall considerably affects blade unsteady aerodynamic loads.